2015
DOI: 10.1186/s12879-015-1101-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology study of Mycobacterium tuberculosis and its susceptibility to anti-tuberculosis drugs in Indonesia

Abstract: BackgroundGenotyping of Mycobacterium tuberculosis helps to understand the molecular epidemiology of tuberculosis and to address evolutionary questions about the disease spread. Certain genotypes also have implications for the spread of infection and treatment. Indonesia is a very diverse country with a population with multiple ethnicities and cultures and a history of many trade and tourism routes. This study describes the first attempt to map the molecular epidemiology of TB in the Indonesian archipelago.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
0
15
2
4
Order By: Relevance
“…Endonezya'da Lisdawati ve ark. (11) 262 izolatla yapmış oldukları çalış-mada 14 (% 5.4) suşun ÇİD-MTK olduğu sonucuna varmışlardır.…”
Section: Discussionunclassified
“…Endonezya'da Lisdawati ve ark. (11) 262 izolatla yapmış oldukları çalış-mada 14 (% 5.4) suşun ÇİD-MTK olduğu sonucuna varmışlardır.…”
Section: Discussionunclassified
“…The male/female sex ratio in Hebei reached 2.26 (705/312), which is higher than the average level. A strong opinion claimed the gender bias in TB infection, which means that the prevalence of TB was higher in men than in women [ 32 ]. In comparison to new cases, we found that the proportion of males in the retreatment panel was significantly larger than females.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recently, a genotyping study of Mycobacterium tuberculosis (MTB) was performed in Indonesia to reveal the TB molecular epidemiology and showed a high genetic diversity that varied by geographical aspects and found that the Beijing strain was the predominant strain in Indonesia. 2 …”
Section: Introductionmentioning
confidence: 99%